2022
DOI: 10.37391/ijeer.100213
|View full text |Cite
|
Sign up to set email alerts
|

On the Connection of Matroids and Greedy Algorithms

Abstract: Matroids are the combinatorial structure and Greedy algorithmic methods always produces optimal solutions for these mathematical models. A greedy method always selects the option that looks best at each step of process of finding optimal solution. In other words, it selects a choice which is optimal choice locally in such a strategy that this locally chosen option may direct to a solution that will be globally optimal. It is true that while selecting locally optimal solution at each stage, Greedy algorithms ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been proposed that zinc has anticancer effects, inhibiting the growth of cancer cells and activating apoptosis. Some studies have reported serum zinc levels to be higher in cancer patients than in others [32][33][34], whereas other studies have reported that it is lower [35]. Some studies suggest that dietary zinc has chemo-preventive properties.…”
Section: Zincmentioning
confidence: 99%
“…It has been proposed that zinc has anticancer effects, inhibiting the growth of cancer cells and activating apoptosis. Some studies have reported serum zinc levels to be higher in cancer patients than in others [32][33][34], whereas other studies have reported that it is lower [35]. Some studies suggest that dietary zinc has chemo-preventive properties.…”
Section: Zincmentioning
confidence: 99%